Hambatan Keterbukaan Diri dengan Teman Sebaya: Studi Kasus Dua Siswa SMK - Rakhmawati Oktaviani; Ma'rifatin Indah Kholili; Agus Tri Susilo (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: This study aims to reveal and describe the factors that influence self-disclosure, the way students express themselves, and the impact of self-disclosure on students who have communication difficulties in peer groups. This research is a case study with snowball sampling participants. The research subjects were DS and R. The data collection techniques were interviews, observation, and documentation. Validation of research data using triangulation of sources and techniques. The results showed that the factors that influence students' self-disclosure are the character of friends, the desire to give reciprocity, fear of not being accepted in expressing opinions to friends, difficulty socializing with friends in class, and understanding the topic. Students also open themselves up by paying attention to situations and conditions, are willing to pay attention to friends when expressed by listening and giving feedback, and are aware of the risks obtained before conveying something to friends. The impact of self-disclosure for DS is being ignored by his classmates, and R is embarrassed to open up with his female friends.